2022
DOI: 10.1007/s13300-022-01255-7
|View full text |Cite
|
Sign up to set email alerts
|

Biosimilar Insulin Aspart Premix SAR341402 Mix 70/30 Versus Originator Insulin Aspart Mix 70/30 (NovoMix 30) in People with Diabetes: A 26-Week, Randomized, Open-Label Trial (GEMELLI M)

Abstract: Introduction This study compared the efficacy, safety, and immunogenicity of biosimilar insulin aspart premix SAR341402 Mix 70/30 (SAR Asp -Mix) with European-approved insulin aspart mix 70/30 − NovoMix® 30 (NN-Mix) in people with type 1 (T1D) or type 2 diabetes (T2D). Methods This 26-week, open-label, phase 3 trial enrolled 402 people with T1D ( n = 105) or T2D ( n = 297) previously treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(26 citation statements)
references
References 18 publications
6
20
0
Order By: Relevance
“…In GEMELLI M, adults with type 1 diabetes (T1D) or type 2 diabetes (T2D) were pretreated with commercial premix NN-Mix or insulin lispro mix (Humalog Mix 25/Liprolog Mix 25, Eli Lilly) therapy. Results for the total study population following treatment for 26 weeks have been previously reported and confirm that SAR Asp -Mix and NN-Mix have similar efficacy, safety, and immunogenicity profiles [ 5 ].…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…In GEMELLI M, adults with type 1 diabetes (T1D) or type 2 diabetes (T2D) were pretreated with commercial premix NN-Mix or insulin lispro mix (Humalog Mix 25/Liprolog Mix 25, Eli Lilly) therapy. Results for the total study population following treatment for 26 weeks have been previously reported and confirm that SAR Asp -Mix and NN-Mix have similar efficacy, safety, and immunogenicity profiles [ 5 ].…”
Section: Introductionsupporting
confidence: 78%
“…Detailed methods of the trial have been previously reported [ 5 ]. In brief, GEMELLI M was a randomized, open-label, multinational, multicenter, active-controlled, parallel-group, phase 3 trial initiated in July 2019 and completed in August 2020.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations